Reviled, Repressed, Resurrected: Vienna 1900 in the Nazi Imaginary. (May 2022) - Morowitz, Laura
Abstract: Encompassing the final decades of Habsburg rule and the rise of modern culture, the cosmopolitan and Jewish Vienna of the fin de siècle was a despised locus in the Nazi historical imaginary. Vienna 1900 was a polyglot, multicultural city, a place where European Jewry had risen to unforeseen heights of economic prosperity and cultural influence; many Nazi ideologues, historians, and authors focused on the verjudet nature of late imperial Vienna. A variety of strategies were employed to distance the Nazi present from Vienna 1900; it was alternately suppressed and ignored, or deeply vilified. Yet the period was also inseparable from two figures celebrated in Nazi Vienna: Mayor Karl Lueger and artist Gustav Klimt. This article examines Nazi discourse on Vienna 1900, especially that originating from Viennese writers, ideologues, and political figures. Reflecting both scholarly and popular views, I examine academic texts, books for popular readers, films, and art exhibitions. After examining the perception and appropriation of Vienna 1900 between the years 1938 and 1945, I end by exploring its instrumentalization in a different context. In an ironic twist of history, the very period suppressed and derided in Nazi discourse would in turn be called upon, by the 1970s, to distract from the shadow of the Nazi era that still hung over the city.